Synthetic Cells: Synthetic Cells Synthesize Therapeutic Proteins inside Tumors (Adv. Healthcare Mater. 9/2018). Issue 9 (9th May 2018) - Krinsky, Nitzan; Kaduri, Maya; Zinger, Assaf; Shainsky‐Roitman, Janna; Goldfeder, Mor; Benhar, Itai; Hershkovitz, Dov; Schroeder, Avi
Abstract : Synthetic cells are artificial systems capable of replacing malfunctioning cells inside the body. This study describes the development of remotely‐activated synthetic cells and their capacity to treat disease. These cell‐sized artificial systems contain all the molecular machinery necessary for transcription and translation, including – ribosomes, RNA polymerase, amino acids and energy. Avi Schroeder and co‐workers present this work in article1701163 . Here, synthetic cells are programmed to produce therapeutic proteins inside tumors, eradicating the surrounding cancer cells.